The Relationship Between Parental Involvement and Students’ Academic Achievement in Rural Areas - Jumiyah, Rahmi; Yulita, Ona; Mastika, Mastika; Ningsih, Nuristi; Khairani, Juhesmi; Siregar, Ripa Hannum (World Psychology, 2025)
Parental involvement has long been recognized as a crucial factor in enhancing students’ academic achievement. However, its impact in rural areas, where access to educational resources and parental education levels may differ significantly from urban settings, remains underexplored. This study examines the relationship between parental involvement and students’ academic performance in rural areas, aiming to identify specific parental behaviors that influence academic success in these communities. A mixed-methods approach was employed, combining quantitative surveys with qualitative interviews. The survey, conducted with 200 parents and 200 students from rural schools, measured levels of parental involvement across various domains, including homework support, communication with teachers, and participation in school activities. Academic achievement was assessed using students’ GPA scores. The results indicated a strong positive correlation between parental involvement and students’ academic performance, with homework support and teacher communication emerging as the most significant factors. Qualitative data revealed that parents’ limited educational backgrounds and work schedules posed challenges to involvement, yet many expressed a commitment to supporting their children’s education. The study concludes that increasing parental engagement in rural areas can significantly improve students’ academic outcomes. Interventions aimed at providing support and resources for parents in these areas are essential for fostering better educational environments.